Using graphic productions in medical — neuropsychological, psychiatric and neurological — diagnosis - Skubisz-Ślusarczyk, Sylwia (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The problems indicated in the present publication result from various malfunctions or deficits caused e.g. by craniocerebral traumas. The sick persons struggle with numerous consequences of such traumas which directly translate into, amongst others, the spoken and written communication process. Apsychological, neuropsychological, neurological and psychiatric diagnosis is asource of valuable information about the disease progress and suspension, or the effectiveness of the implemented therapy. The application of modern research views and positions contributes to the development of more effective impacts directing and supporting patients in their endeavour to live in dignity.This publication is addressed primarily to students as ateaching aid during the forensic, criminal or civil procedure courses, but also to practitioners who – for their professional purposes – appoint handwriting experts, and who seek knowledge about handwriting research.
Keywords: pismo ręczne; badanie pisma ręcznego; ekspertyza pismoznawcza; ekspert; urazy czaszkowo-mózgowe; zaburzenia komunikacji w mowie i piśmie; diagnoza lekarska; diagnoza psychologiczna; neuropsychologia; psychiatria; neurologia